Exploring the Synergy between Cellobiose Dehydrogenase from Phanerochaete chrysosporium and Cellulase from Trichoderma reesei - Wang, Min; Lu, Xuefeng (Frontiers in Microbiology, 2016)
Recent demands for the production of lignocellulose biofuels boosted research on cellulase. Hydrolysis efficiency and production cost of cellulase are two bottlenecks in “biomass to biofuels” process. The Trichoderma cellulase mixture is one of the most commonly used enzymes for cellulosic hydrolysis. During hydrolytic process cellobiose accumulation causes feedback inhibition against most cellobiohydrolases and endoglucanases. In this study, we demonstrated the synergism effects between cellobiose dehydrogenase (CDH) and cellulase both in vitro and in vivo. The CDH from Phanerochaete chrysosporium was heterologously expressed in Pichia. pastoris. Supplementation of the purified CDH in Trichoderma cellulase increased the cellulase activities. Especially β-glucosidase activity was increased by 30%-100% varying at different time points. On the other hand, the cdh gene was heterologously expressed in Trichoderma reesei to explore the synergism between CDH and cellulases in vivo. The analyses of gene expression and enzymatic profiles of filter paper activity (FPA), carboxymethylcellulase (CMCase) and β-glucosidase show the increased cellulase activity and the enhanced cellulase production in the cdh-expressing strains. The results elucidate a possible mechanism for diminishing the cellobiose inhibition of cellulase by CDH. These findings provide a novel perspective to make more economic enzyme cocktails for commercial application or explore alternative strategies for generating cellulase-producing strains with higher efficiency.